2021
DOI: 10.3390/jcm10040620
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 Pandemic on Maternal Anxiety in Brazil

Abstract: Background: The coronavirus disease 2019 (COVID-19) pandemic may have an effect on maternal anxiety and influence postpartum experience. Objective: To study the prevalence of maternal anxiety in late pregnancy in the context of the COVID-19 outbreak in Brazil and to analyze its association with maternal knowledge and concerns about the pandemic. Methods: This was a national multicenter cross-sectional study performed in 10 different public university hospitals, between 1 June and 31 August 2020, in Brazil. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 29 publications
1
31
0
5
Order By: Relevance
“…Previous studies have obtained similar results, confirming the association between breastfeeding and maternal mental health [14]. Given the increased risk of mental health issues during a pandemic, both in the general population [15] and especially in mothers [16], it is clear that breastfeeding is of fundamental importance for maternal well-being during this pandemic. Breastmilk is also known to have a strong immune value.…”
Section: Support Of Breastfeeding During the Covid-19 Pandemicsupporting
confidence: 67%
“…Previous studies have obtained similar results, confirming the association between breastfeeding and maternal mental health [14]. Given the increased risk of mental health issues during a pandemic, both in the general population [15] and especially in mothers [16], it is clear that breastfeeding is of fundamental importance for maternal well-being during this pandemic. Breastmilk is also known to have a strong immune value.…”
Section: Support Of Breastfeeding During the Covid-19 Pandemicsupporting
confidence: 67%
“…Uma pesquisa sobre ansiedade materna e pandemia mostrou em seus resultados que a região Centro-Oeste (junto com o Sul), na qual se encontra o Brasília, teve a maior prevalência de ansiedade e gravidade -nesta região, 39% das entrevistadas apresentaram sintomas classificados entre moderados ou severos, a maior taxa brasileira (Nomura et al 2021) Demais aspectos apresentados por diferentes estudos apontam para alguns fatores que podem contribuir para o aumento da ansiedade durante a pandemia, dentre eles o excesso de informação sobre o surto da COVID-19. Destacam ainda que a busca por informação atualizada é uma tentativa de se sentir seguro, porém o consumo exacerbado de informação tem gerado mais insegurança.…”
Section: O Acolhimento E As Primeiras Demandasunclassified
“…So far, there are studies, systematic reviews, and meta-analyses in which the prevalence of pregnant women with moderate to severe anxiety during the COVID-19 pandemic is given more precisely (Corbett et al, 2020 ; Hessami et al, 2020 ; Lebel et al, 2020 ; Mappa et al, 2020 ; Saccone et al, 2020 ; Fan et al, 2021 ; Sun et al, 2021 ; Tomfohr-Madsen et al, 2021 ). Accordingly, it ranges from: 23.4% found in Brazil (Nomura et al, 2021 ); the 29% was determined during the initial stage of the COVID-19 pandemic in China (Wang et al, 2020 ), while 25% was determined by meta-analysis (Ren et al, 2020 ); the 38% was found in Poland (Nowacka et al, 2021 ); the elevated level of the trait (38.2%) and state anxiety (77%) was found in Italy (Mappa et al, 2020 ). Higher prevalence in the range from 53 to 72% was found in other countries (Corbett et al, 2020 ; Dagklis et al, 2020 ; Davenport et al, 2020 ; Hessami et al, 2020 ; Lebel et al, 2020 ; Saccone et al, 2020 ; Sut and Kucukkaya, 2020 ).…”
Section: Introductionmentioning
confidence: 99%